God's library the archaeology of the earliest Christian manuscripts - Nongbri, Brent 1977- (New Haven, CT Yale University Press, 2018)
Frontmatter -- Contents -- Acknowledgments -- Map Showing Locations in Egypt -- Prologue: Reintroducing the Earliest Christian Manuscripts -- 1. The Early Christian Book -- 2. The Dating Game -- 3. Finding Early Christian Books in Egypt -- 4. A Discovery "Which Threw All Others in the Shade": The Beatty Biblical Papyri -- 5. An Elusive Collection: The Bodmer Papyri -- 6. Excavating Christian Litter and Literature at Oxyrhynchus -- 7. Fabricating a Second-Century Codex of the Four Gospels -- Epilogue: The Future of Ancient Christian Books -- Appendix: Christian Books from Oxyrhynchus -- Notes -- Bibliography -- Index of Subjects -- Index of Manuscripts
In this bold and groundbreaking book, Brent Nongbri provides an up-to-date introduction to the major collections of early Christian manuscripts and demonstrates that much of what we thought we knew about these books and fragments is mistaken. While biblical scholars have expended much effort in their study of the texts contained within the earliest Christian manuscripts, there has been a surprising lack of interest in thinking about these books as material objects with individual, unique histories. We have too often ignored the ways that the antiquities market obscures our knowledge of the origins of these manuscripts. Through painstaking archival research and detailed studies of the most important collections of early Christian manuscripts, Nongbri vividly shows that the earliest Christian books are more than just carriers of texts or samples of handwriting. They are three-dimensional archaeological artifacts with fascinating stories to tell, if we're willing to listen
restricted access online access with authorization star
[Online-Ausgabe]
Mode of access: Internet via World Wide Web.
In English
Keywords: Christian literature, Early -- Manuscripts -- Antiquities; Christianity -- Origin; Manuscripts, Greek (Papyri) -- Antiquities; Religion / History; RELIGION / Biblical Studies / History & Culture